(3GdPNjQI aj abg GdeGdcjIs - (3CHhGdYHGS TgGH GdOjf CMeO Hf GOQjS Hf YHO GdQMef GdUfgGLj GdbQGaj GdeGdcj,J (B684 (3g` s ((3YHO Gdedc Hf eMeO Hf YHO Gdedc GdMVQei s)
(3ChdgG (B:s
(3jHOC HaQY GdbUGU Hbhdg (B: (3hTQY ef bHdfG TQY dfG hGdQLd HGdeQCI hGdeQCg HGdQLd s
(3BNQgG (B:s
(3jfJgi HaQY ef CMcGe GdhUGjG Hbhdg (B: (3caGQGJ GdbJd hGdXgGQ hSGjQ GdCfhGY jWdH Gdfbd Gdfbd hZjQg HGdaQhK GdabgjI Je GdSaQ GdNGeS s
(3jTJed Ydi HbjI cJGH GdLfGjGJ hcJGH GdaQGFV hcJGH GdLGeYs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B94 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B158s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs